The Interconnection of Traditional and Modern Approaches in Wahbah al-Zuḥailī’s al-Tafsīr al-Munīr - Muhammad Naufal Hakim; Imroatul Azizah; Moh. Yardho; Tri Febriandi Amrulloh (Universitas Islam Negeri Imam Bonjol Padang, 2024)
This article aims to examine the construction of the methodology of al-Tafsīr al-Munīr by Wahbah al-Zuḥailī in both technical and hermeneutical aspects, and subsequently evaluate its position within the discourse of contemporary Quranic interpretation. To achieve this objective, the research employs an exegesis approach with Islah Gusmian theory of Quranic interpretation methodology and Abdul Mustaqim theory of typology of contemporary Quranic interpretation as analytical tools. The study concludes that the construction of the methodology of al-Tafsīr al-Munīr, whether viewed from technical or hermeneutical aspects, involves efforts to balance textual analysis and contextual exploration through consistent and scientific systematization, authoritative reference sources, integration of naql (textual sources) and ‘aql (reason), interdisciplinary and intertextual thinking methods, diverse nuances, and textual-reflective approaches. Based on these findings, it can be assessed that Wahbah al-Zuḥailī has succeeded in bridging traditional text-oriented approaches with modern context-oriented approaches, making al-Tafsīr al-Munīr typologically categorized as a moderate interpretation within the discourse of contemporary Quranic interpretation.